2013
DOI: 10.1016/j.toxlet.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Human exposure to mycotoxins and their masked forms through cereal-based foods in Belgium

Abstract: In the present study, a quantitative dietary exposure assessment of mycotoxins and their masked forms was conducted on a national representative sample of the Belgian population using the contamination data of cereal-based foods. Cereal-based food products (n = 174) were analysed for the occurrence of deoxynivalenol, 3-acetyldeoxynivalenol, 15-acetyldeoxynivalenol, zearalenone, α-zearalenol, β-zearalenol, T-2-toxin, HT-2-toxin, and their respective masked forms, including, deoxynivalenol-3-glucoside, zearaleno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(89 citation statements)
references
References 46 publications
7
79
1
2
Order By: Relevance
“…According to the latest occurrence papers (see De Boevre et al 2013), the modified forms of ZEN (ZELs, ZEN14Glc, ZEN14Sulf, βZEL14Glc, αZEL14Glc) commonly occur together with their precursor in cereal-based food, mainly in bran-and fibre-enriched products. The percentage of occurrence with respect to ZEN ranges from 15 to 110 %, expressed as the sum of all the co-occurring modified forms in each sample (see Section 8, Table 6).…”
Section: Exposure To Zearalenone and Its Modified Formsmentioning
confidence: 99%
“…According to the latest occurrence papers (see De Boevre et al 2013), the modified forms of ZEN (ZELs, ZEN14Glc, ZEN14Sulf, βZEL14Glc, αZEL14Glc) commonly occur together with their precursor in cereal-based food, mainly in bran-and fibre-enriched products. The percentage of occurrence with respect to ZEN ranges from 15 to 110 %, expressed as the sum of all the co-occurring modified forms in each sample (see Section 8, Table 6).…”
Section: Exposure To Zearalenone and Its Modified Formsmentioning
confidence: 99%
“…(Sirot et al, 2013;Sprong et al, 2016b). For the exposure assessment studies, food consumption data were mainly obtained from national food consumption surveys, including different data collection methodologies, namely 1-day (Cressey and Reeve, 2013;Han et al, 2014), 2-day (De Boevre et al, 2013;Sprong et al, 2016a;Van de Perre et al, 2015) and 3-day 24-hour recalls (Zhao et al, 2015), 3-day food diary and 7-day food diary (Sirot et al, 2013), all reported in Table 2.…”
Section: Worldwide Exposure Assessment Of Co-occurring Mycotoxins In mentioning
confidence: 99%
“…Although, some authors decided also to include the LOQ in the management of non-detects (García-Moraleja et al, 2015;Sirot et al, 2013). Until now, the assessment of mycotoxin exposure is mainly based on deterministic approaches, however, there are an increasing number of studies applying probabilistic models in last years, as shown in Table 2 Cano-Sancho et al, 2013;De Boevre et al, 2013;Han et al, 2014;Signorini et al, 2012;Van de Perre et al, 2015).…”
Section: Worldwide Exposure Assessment Of Co-occurring Mycotoxins In mentioning
confidence: 99%
See 2 more Smart Citations